Availability and Performance Evaluation of Vehicular Ad Hoc Networks - Silva, Luis Guilherme; Silva, Francisco Airton (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2026: Anais Estendidos do XLIV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2026)
Urban mobility demands continuity of service, dynamic adaptation, and fault tolerance in distributed computing architectures. In this context, Vehicular Ad Hoc Networks (VANETs) integrated with edge computing support traffic monitoring and control applications under varying operational conditions, while resource constraints in Road Side Units (RSUs) make strategies based on physical replication unfeasible. Given this scenario, this dissertation develops analytical models based on Stochastic Petri Nets to evaluate the availability, performance, and sustainability of a VANET architecture composed of multiple RSUs connected to an edge server. The availability analysis considers physical, logical, and communication failures, evaluating operational continuity through virtual machine migration, with reduced recovery time even under simultaneous failures. The performance evaluation models horizontal autoscaling with reinstantiation, highlighting degradation of the average response time and an increase in the discard rate when scaling limits are inadequate, and better operational balance with dynamic policies. The sustainability analysis incorporates energy and environmental metrics, indicating a reduction in energy consumption and carbon emissions, while adjustments with experimental data from Pasid-Validator confirm the adherence between analytical and empirical results. In conclusion, the proposed models show that the combination of virtual machine migration and dynamic autoscaling allows maintaining service continuity, controlling performance under load variation, and reducing energy impact, supporting predictive planning of RSU-based VANET architectures.